2009
DOI: 10.1002/hyp.7470
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological modelling of Ethiopian catchments using limited data

Abstract: Abstract:The hydrological component of the soil and water assessment tool (SWAT) model is adapted for two Ethiopian catchments based on primary knowledge of the coherence spectrum between rainfall and stream flow data. Spectrum analysis using the available nearby climatic data is made to limit the temporal and spatial scales (inverse rate coefficients) subject to the calibration of compartmentalized runoff models. The exclusion of unwarranted time scales in the calibration implies that the model efficiency (r … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Further, the paper reported that more than 60 % of the observed river discharge falls within the 95 % confidence bounds. Mekonnen et al (2009) developed a generic rainfall-runoff model better suited to Ethiopian catchments. They used a spectrum analysis method to extract the relationships between different temporal scales of available daily rainfall and runoff series that reflect the temporal and spatial scales of 25 discharges in two watersheds in Ethiopia.…”
Section: Model Calibration Parameterization and Validationmentioning
confidence: 99%
“…Further, the paper reported that more than 60 % of the observed river discharge falls within the 95 % confidence bounds. Mekonnen et al (2009) developed a generic rainfall-runoff model better suited to Ethiopian catchments. They used a spectrum analysis method to extract the relationships between different temporal scales of available daily rainfall and runoff series that reflect the temporal and spatial scales of 25 discharges in two watersheds in Ethiopia.…”
Section: Model Calibration Parameterization and Validationmentioning
confidence: 99%
“…The Soil Water Assessment Tool (SWAT) (Arnold et al, 1998) is a leading model that belongs to this category. A review article by Gassman et al (2007) pointed out the fundamental strength of SWAT model as a comprehensive package of hydrological and hydraulic processes that allowed its widespread use in the simulation runoff and water yield (Anand et al, 2007;Mekonnen et al, 2009) and soil water content (Deliberty and Legates, 2003;Mapfumo et al, 2004;Narasimhan et al, 2005), the evaluation of the effect of agricultural and structural BMPs on water quality (Stewart et al, 2006;Gollamudi et al, 2007;Gitau et al, 2008) and the assessment of the effectiveness of structural BMPs on reducing soil erosion (Bracmort et al, 2006;Yang et al, 2009). Gassman et al (2007) recognized that SWAT's strength also reflects its weakness in the sense that empirical and semiempirical depictions of some processes may be overly simplified and require further refinement.…”
Section: Introductionmentioning
confidence: 99%
“…It is a freely available public domain model and has been validated for different catchments in different parts of the world (Pikounis et al 2003;Jayakrishnan et al 2005;Ahl et al 2008). However, there are only few applications of the SWAT model to Ethiopian conditions (Tadele and Foerch 2007;Mekonnen et al 2009;Setegn et al 2009aTessema et al 2014). Few water-related research studies were conducted on the upper Awash River basin (Hailemariam 1999;Chekol 2006).…”
Section: Introductionmentioning
confidence: 99%